REFLEKSI SEMANGAT BUSHIDO DALAM CERITA ANAK TURUSIENNGI PAPPASENNA TOMATOANNA (The Reflection of Bushido’s Spirit in Anak Turusienngi Pappasenna Tomatoanna Story) - Murmahyati Mahmud (Balai Bahasa Sulawesi Selatan, 2009)
This writing describes the reflection of Bushido’s spirit in Anak TurusienngiPappasenna Tomatoanna’s story. Bushido’s spirit is the secret regarding thesuccessful of Japanese people. Data is analyzed by using descriptive method, whilethe analysis result found that the successful of La Tinulu the central character inthe story has been the reflection of Bushido’s spirit.